Balloon pin‐hole rupture during percutaneous coronary intervention for recurrent, calcified in‐stent restenosis: A case report. Issue 7 (13th November 2017) - Murata, Nobuhiro; Takayama, Tadateru; Hiro, Takafumi; Hirayama, Atsushi
Abstract: Percutaneous coronary intervention (PCI) for patients with in‐stent restenosis (ISR) is generally considered safe and effective. However, due to increased tissue hardness, PCI for calcified intra‐stent ISR is technically challenging. Here, we report severe angioplasty‐related complications in a patient presenting with calcified, recurrent ISR following PCI. After receiving drug‐coated balloon (DCB) angioplasty for an initial ISR, the patient developed recurrent ISR during the follow‐up period. Intravascular imaging revealed intra‐stent calcifications and balloon angioplasty was subsequently performed. During the angioplasty, a pin‐hole balloon rupture occurred, consequently causing coronary dissection as visualized by intravascular imaging. To prevent acute coronary occlusion, stent implantation was required. The present case report suggests that, following detection of intra‐stent calcified stenosis, both careful balloon inflation as well as optimal ablation device selection are required to prevent potential complications and obtain successful procedural outcomes.